Lineage divergence of activity-driven transcription and evolution of cognitive ability - Hardingham, Giles E.; Pruunsild, Priit; Bading, Hilmar (Nature reviews. Neuroscience, 2018)
Excitation-transcription coupling shapes network formation during brain development and controls neuronal survival, synaptic function and cognitive skills in the adult. New studies have uncovered differences in the transcriptional responses to synaptic activity between humans and mice. These differences are caused both by the emergence of lineage-specific activity-regulated genes and by the acquisition of signal-responsive DNA elements in gene regulatory regions that determine whether a gene can be transcriptionally induced by synaptic activity or alter the extent of its inducibility. Such evolutionary divergence may have contributed to lineage-related advancements in cognitive abilities.